Application of citrus agroindustry residue for the production of hydrogen using pure and mixed cultures - Silva, Daiana Camila da [UNESP]; Adames, Luan Vieira [UNESP]; Pires, Lorena Oliveira [UNESP]; Costa Marques, Rodrigo Fernando [UNESP]; Tallarico Adorno, Maria Angela; Maintinguer, Sandra Imaculada [UNESP] (Univ Fed Rio De Janeiro, Lab Hidrogenio, 2021)
In recent years there has been a growing interest in the use of various agro-industrial wastes. In Brazil, the food industries accumulate an enormous amount of waste, especially those that process citrus fruits. Among the possibilities for valuing these residues, anaerobic digestion is a promising alternative in the generation of renewable energy and pollution control. In this sense, this study evaluated the anaerobic digestion of citrus wastewater, aiming at the biological production of hydrogen from three inocula: (1) Clostridium Acetobutylicum ATCC 824, (2) Clostridium Beijerinckii ATCC 10132 and (3) anaerobic consortium obtained from citrus wastewater. The experiment was carried out in 51h, in triplicates of anaerobic batch reactors, fed with 2 different carbon sources: glucose (10.7 g COD L-1) and citrus wastewater (10.0 g COD L-1), headspace filled with N-2 (99.99%), initial pH 7.0 and maintained at 37 degrees C, under static mode. In the reactors fed with glucose, hydrogen generation was verified only with the inocula 1 and 2, which were, respectively, 36.8 mmol L-1 and 64.1 mmol L-1. In the reactors operated with citrus wastewater, were obtained 21.2; 15.7 e; 37.6 mmol H-2 L-1 with inocula 1; 2 and 3, respectively. In addition, expressive generations of ethanol were verified for all inocula tested in the reactors fed with glucose. In the characterization of the citrus anaerobic consortium, a predominance of Gram + bacilli was verified and the genera of anaerobic H-2-generating bacteria (UFC mL(-1)) were quantified: Clostridium sp. (3x10(5)), Bacteroides sp. (4x10(5)), Lactobacillus sp. (4x10(5)), Streptococcus sp. (5x10(4)), and Veillonella sp. (3x10(5)), revealing a high diversity of anaerobic hydrogen-producing bacteria present in agro-industrial wastewater. Such results emphasize that the generation of hydrogen can occur in different metabolic pathways with consequent favor in the generation of biofuels such as ethanol or butanol.
Keywords: Wastewater; Citrus; Fermentation; Clostridium